The Concept of Justice in the Determination of Murabahah Margin in BPRS: Normative Analysis of Sharia Economics - Istiqomah; Tri Hidayati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This article examines the concept of justice in determining the margin of murabahah in Sharia People's Financing Banks (BPRS) using a normative approach to sharia economics. The focus of the research is directed at the conformity of the practice of determining margins with the principles of fiqh muamalah, maqashid al-sharia, as well as applicable regulations, especially the DSN-MUI Fatwa and OJK regulations. The results of the analysis show that although normatively the margin of murabhah should be based on cost of goods transparency, voluntary agreements, and information disclosure, practices in the field are still influenced by conventional benchmarks such as market interest rates and internal decisions of the Asset Liability Committee (ALCO). This situation has the potential to cause an identity crisis for Islamic financial institutions and weaken the principle of ridha bi al-taradhi. This study emphasizes the urgency of preparing national guidelines for determining margins based on maqashid al-sharia, the implementation of a more participatory negotiation mechanism between banks and customers, and increasing transparency through accountable written documents. Thus, this article contributes to strengthening the identity and legitimacy of Islamic banking while offering a normative framework as an alternative to pragmatic, market-oriented practices.